Harley-Davidson: creating experience from strategy - Grant, Robert (Henry Stewart Talks, 2018)
This case study considers Harley Davidson’s business strategy transition during the late 1990s. As Harley Davidson had suffered prolonged lack of investment, its resource capabilities significantly lagged that of its rivals. However, by focusing on supplying the ‘Harley Davidson experience’ rather than simply motorcycles, the company successfully nullified the technological edge enjoyed by its competitors.